The Effect of Several Electric Cigarette Puffs on Nanohybrid Composite Resin Surface Roughness - Amaliyah, Alvi Rizqi; Widodo, Haris Budi; Dwiandhono, Irfan (UI Scholars Hub, 2023)
Nanohybrid composite resin is a dental restorative material comprising micro and nano-sized fillers. When accompanied by smoking habits, it can alter the surface roughness of composite resin. Objective: This study aimed to determine the effect of several electric cigarette (e-cigarette) puffs on the surface roughness of nanohybrid composite resin. Methods: This study was conducted in the experimental laboratory with a pretest-posttest control group design using 48 nanohybrid composite resin specimens divided into six groups. Subsequently, the experimental groups were exposed to 75, 150, 225, 300, and 450 puffs of e-cigarette, and the control group was given artificial saliva immersion without exposure for 21 days. The surface roughness of specimens was measured with a surface roughness tester and evaluated through statistical analysis, including One-Way ANOVA and Post-Hoc LSD. Results: The average pre-test and post-test differences between groups I, II, III, IV, V, and VI were 0.013, 0.022, 0.033, 0.044, 0.065, and 0.005 μm. These results showed a significant difference in the surface roughness of nanohybrid composite resin (p < 0.05), with variations between all groups. Conclusion: This study showed that the number of e-cigarette puffs had a significant effect on the surface roughness of nanohybrid composite resin. Specifically, an increase in the number of e-cigarette puffs led to a rise in the surface roughness value of nanohybrid composite resin.